Lipiodol accumulation pattern as imaging biomarker of tumoral response after conventional transarterial chemoembolization and survival outcome in hepatoccellular carcinoma patients - Azizi, Mohd Yadie Syazwan (2021)
Background: TACE is the locoregional treatment of choice for unresectable hepatocellular carcinoma, and a successful procedure would improve the survival rate of the patient. Good antitumoral coverage in the targeted liver tumor is necessary to produce good tumoral necrosis and results in a good therapeutic effect. TACE by using a mixture of anticancer and iodized oil (Lipiodol) may provide an overview of the degree of accumulation and retention within the targeted tumor on subsequent CT-scans follow up, thus predicting the outcome of the treatment. This study aimed to determine the correlation between the pattern of accumulation pattern of lipiodol and the targeted tumoral response toward the treatment given and the overall survival rate of HCC patients. Methods: This retrospective record review was done from 2013 until 2020 in patients who received TACE with anticancer and Lipiodol in Hospital Universiti Sains Malaysia, who are fulfilling inclusion and exclusion criteria. Lipiodol accumulation pattern is observed approximately after six weeks post-TACE on the follow-up CT scans and later is classified into 4 accumulation patterns; pattern 4, complete accumulation; pattern 3, intense (>75% of tumor volume); pattern 2, moderate (<75% of tumor volume); and pattern 1 – low accumulation. Evaluation of the tumoral response was done according to the mRECIST criteria. Chi-Square or Fischer Exact test and multiple logistic regression test analysis was used to determine the association between the lipiodol accumulation pattern and the tumor response towards the treatment. A survival analysis test (Kaplan-Meier analysis) was used to determine the association between the accumulation pattern and the overall survivability of the patient who received TACE. Simple and Multiple Cox Proportional Hazard Regression tests were used to study other associated factors affecting overall survivability. Results: A total of data from 38 subjects were obtained in both BCLC stage B (n=33) and BCLC stage C (n=10) groups. In BCLC stage B, 18% (n=7) were in complete accumulation, 26% (n=10) in intense accumulation, 16% (n=6) in moderate accumulation and 13% (n=5) in low accumulation pattern. Fisher’s exact test for BCLC stage B subjects showed significant association between lipiodol accumulation pattern and tumor response with Fisher’s Exact value of 27.025 (p<0.001). Spearman-rho test reports a significant association of lipiodol accumulation pattern and tumor response with a magnitude of 0.84 in this group. In BCLC stage C no complete accumulation pattern was observed, 5% (n=2) were in intense accumulation, 11% (n=4) were in moderate accumulation and 11% (n=4) were in low accumulation pattern. The Fisher’s exact test for subjects in BCLC Stage C showed no significant association between lipiodol accumulation pattern and tumor response with Fisher’s Exact value 2.281 (p>0.05). Survival analysis shows higher proportion of cases survived at 1- year and 3-year in complete (85.7% at 1-year and 17.1% at 3-year) and intense (88.9% at 1- year and 38.1% at 3-year) lipiodol accumulation group in BCLC stage B group as compared to other accumulation patterns. The median survival time in BCLC stage B for each group were 26 months (complete), 30 months (intense), 9 months (moderate) and 16 months (low). In BCLC stage C group where only moderate and low accumulation pattern were observed above one year, with 1-year survival rate was 50% (moderate) and 25% (low) with none survive at three and five years. The median survival time for BCLC stage C group were six months (intense), four months (moderate), and eight months (low). Simple and Multiple cox regression analysis revealed that the number of liver nodules group and number of TACE procedures done were among significant prognostic factor of death in HCC. Patients that have 5-9 liver nodules had a 12.1 times higher risk of death as compared to the group of patients with 1-4 liver nodules (HR: 12.1, 95% CI: 1.17 – 124.57). Patients that received one TACE procedure are expected to have a decrease in risk of death by 0.57 (HR: 0.565, 95% CI: 0.393 – 0.812). Though additional regression analysis did not report a significant influence of lipiodol accumulation pattern on disease progression, correlation analysis reported a moderate positive correlation between lipiodol accumulation pattern and disease progression (rs(36) = 0.796, p < 0.001). Conclusion: Lipiodol deposition in liver tumors can be evaluated using quantitative baseline imaging characteristics and it shows significant correlation with tumor response toward the treatment and influence the survival outcome of the patients. Our study confirms the findings of previous studies and validates the unique properties and function of Lipiodol as a tumorspecific, drug-carrying, and imaging biomarker agent to treat HCC patients.